P–176 Effects of high non-esterified fatty acids exclusively during bovine in vitro fertilization on cell lineage allocation of blastocysts. (6th August 2021) - Idriss, A; Okello, E; Roger, S; Velazquez, M
Abstract: Study question: Are there effects of high non-esterified fatty acids exclusively during bovine in vitro fertilization on cell lineage allocation of blastocysts? Summary answer: Under the conditions of the present study, high exposure to NEFA during bovine IVF significantly decreases embryo production and alters cell allocation of resultant blastocysts. What is known already: Cattle models have shown that a high exposure to non-esterified fatty acids (NEFA) such as steric acid (SA), palmitic acid (PA]) and oleic acid (OA) during in vitro oocyte maturation and embryo development can disrupt both embryo formation and quality. However, the fertilization process per se have been less studied, which is needed to identify developmental stages were potential therapies could be develop to ameliorate NEFA toxicity during the periconceptional period Study design, size, duration: Day–8 blastocysts were immunostained for CDX2, a transcription factor involved in trophectoderm differentiation, to examine cell allocation of blastocysts derived from oocytes fertilised under high NEFA levels. VF (19 h) was carried with different NEFA levels(4 replicates) representing physiological (Control–1[C1], 28μM SA, 23μM PA, 21μM OA) and pathophysiological (NEFA, 280μM SA, 230μM PA, 210μM OA) relevant concentrations. A second control (C2) group contained solvent. Blastocysts (C1; n = 14, C2; n = 12, NEFA; n = 8) Participants/materials, setting, methods: All blastocysts were examined by confocal microscopy and cell counting was done with the Imaris software. Data were analysed by ANOVA (mean±SEM) with percentage data arcsine transformed before analysis. Main results and the role of chance: Blastocyst formation was decreased by high NEFA levels (C1=25.6±2.7%, C2=26.0±2.3%, NEFA=9.4±0.4%, P < 0.001) which was associated with a decreased cleavage rate (C1=70.1±6.5%, C2=71.5±3.1%, NEFA=42.5±4.1%, P = 0.006) and an increase in embryo degeneration (C1=47.6±3.5%, C2=47.7±5.8%, NEFA=63.0±4.9%, P = 0.05). A lower total cell (TC) the number was observed in high NEFA-derived blastocyst (C1=125.2±6.6, C2=132.3±8.4, NEFA=67.3±5.6, P < 0.001) associated with a low cell number in both the trophectoderm (CDX2 positive cells, C1=90.2±5.9, C2=96.7±6.4, NEFA=41.3±4.1, P < 0.001) and the inner cell mass (ICM, C1=35.0±2.4, C2=35.7±3.5, NEFA=26.0±2.2, P < 0.001). Furthermore, high NEFA-derived blastocyst showed an increased allocation of cells towards the ICM (ICM/TC proportion, C1=28.2±1.7%, C2=26.9±1.8%, NEFA=39.1±2.2%, P < 0.001) Limitations, reasons for caution: It will be better if the number of blastocysts reached increases. Wider implications of the findings: such research can be widely applied to the human model due to the similarities between both specie. Trial registration number: Royal Embassy of Saudi Arabia Cultural Bureau